Histomorphology of epidermis in adult Jabalpur Black pigs - MAJEED, SHAZIA; PARMAR, M L; KHAN, MASSARAT; SHEIKH-DEVAJUENG, F D (The Indian Journal of Animal Sciences, 2012)
Histomorphological studies of epidermis in 6 adult (Large White Yorkshire×desi crossbred) Jabalpur black pigs was conducted and it was found that epidermis consisted of stratum basale, stratum spinosum, stratum granulosum and stratum corneum. However, epidermal pegs of variable size were observed which was the most characteristic feature in pig skin. The epidermis was the thickest in the dorsal aspect of tail 269.00±23.04µ and thinnest in the ventral aspect 269.00±4.29 µm. A strong alkaline phosphatase activity was seen in the stratum basale and stratum corneum which indicates the presence of calcium deposits in these 2 layers.